Effectiveness of a CuZnNi alloy in preventing microbial growth and biofilm architecture - G.G. Guerini; M.H.R. Suenaga; V.G. Vital; M.R. Silva; V.T. Santos; F.G. Lobo; M.A. Cardoso; F.R. Simões; D.S. Pellosi; S.P. Vasconcellos; R.A.G. Silva (Journal of Materials Research and Technology)
Copper and its alloys are widely used across many industrial sectors due to their diverse properties. They are known to exhibit strong microbicidal properties, primarily due to the oxidative stress caused by copper ions released during metal oxidation, although the exact mechanisms are not fully understood. In this study, we investigated the electrochemical and microbicidal behavior of the Cu68.85Zn26.36Ni4.69 alloy in artificial sweat and 0.5 mol L−1 NaCl solutions, correlating these properties with the alloy microbicidal activity against Escherichia coli (ATCC 8739), Staphylococcus aureus (ATCC 6538), Candida albicans (ATCC 10231), and the biofilm-forming bacterium Pseudomonas aeruginosa (ATCC 9027), with biofilm dispersal capacity also evaluated. The results were promising, indicating that in artificial sweat solution, the corrosion potential of the CuZnNi alloy was less noble compared to pure copper, despite the slightly lower corrosion current density observed in the alloy. Furthermore, the alloy surface predominantly contained Cu+ ions when exposed to air and to the artificial sweat solution. However, this shifted to Cu2+ ions after exposure to biotic media upon direct contact with P. aeruginosa, forming CuO species on the bacterial cell membrane and leading to biofilm damage. Overall, the Cu68.85Zn26.36Ni4.69 alloy showed corrosion resistance in the same order of magnitude as pure copper and a promising antimicrobial efficiency compared to previous literature reports, revealing interesting properties for further applications as a smart material for surface coatings.